Hydrogen embrittlement mechanisms in advanced high strength steel. (15th January 2022) - Gong, Peng; Turk, Andrej; Nutter, John; Yu, Feng; Wynne, Bradley; Rivera-Diaz-del-Castillo, Pedro; Mark Rainforth, W.
Abstract: Hydrogen embrittlement is increasingly important in advanced high strength steels (AHHS) as strength levels increase well above 1000 MPa. This work developed a detailed understanding of the embrittling mechanism in model AHHS steels based on Fe-Ti-Mo and Fe-V-Mo, both strengthened through interphase precipitation. Hydrogen charging led to an increase in the dislocation density and an enlarged strain field around precipitates, resulting in an increase in residual stress. This was much greater for the Ti-Mo steel compared to the V-Mo. Important differences in the hydrogen trapping behaviour was seen between the two steels, with hydrogen believed to be trapped at the matrix/precipitate interface for the Ti-Mo steel, but within the precipitate for the V-Mo steel. The effects of hydrogen were investigated in detail for slow strain rate tensile tests and double notched tensile samples. Hydrogen charging resulted in a loss in strength and ductility, with the Ti-Mo steel failing at yield, while the V-Mo steel exhibited a ∼13% loss in strength and a ∼ 35% loss of ductility. Crack initiation in tensile samples occurred at high strain gradient dislocation boundaries. However, crack propagation rapidly became quasi-cleavage, along the {100} plane in ferrite, and also along the martensite/ferrite grain boundaries on the {110} plane in the martensite. Minimal plasticity was observed associated with the crack tip, which was believed to be a result of the suppression of dislocation emission at the crack tip by the hydrogen. Graphical Abstract: Graphical Abstract Image, graphical abstract .